A parsimonious model for calculating the greenhouse gas emissions of miscanthus cultivation using current commercial practice in the United Kingdom. Issue 7 (9th May 2021) - Lask, Jan; Kam, Jason; Weik, Jan; Kiesel, Andreas; Wagner, Moritz; Lewandowski, Iris
Abstract: Life cycle assessment (LCA) is a widely recognized tool for the assessment of the potential environmental impacts associated with the life cycle of a product or service. The environmental impact category most commonly quantified in LCAs is global warming potential, a measure of greenhouse gas (GHG) emissions. For agricultural products such as miscanthus, the creation of an inventory can be labour‐intensive and is context‐specific. This impairs the transfer of results to comparable but not necessarily similar situations. Farmers and small‐ and medium‐sized enterprises cannot easily dedicate resources for this purpose (in particular when using marginal land) and often lack the expertise to do so. Simplified LCA models could offer a promising solution to this problem. They are simplified versions of more complex models that require only a few critical parameters to calculate representative results. This study develops such a model for the computation of GHG emissions associated with commercial miscanthus cultivation. The model focuses on rhizome‐based propagation and the indirect harvesting method (cutting to swath, swathing, baling). A parametric life cycle inventory (LCI) was established and used to identify the most influential parameters by means of a global sensitivity analysis (GSA). A simplified model for calculating GHG emissions associated with miscanthus cultivation was developed by fixing input parameters with a low relevance at their median impact values. Six of 38 parameters were identified as relevant parameters: soil carbon sequestration, harvestable yield, duration of cultivation period, quantities of nitrogen and potassium fertilizer applied, and distance between field and customer. The simplified model allows practitioners an easy assessment of the GHG emissions associated with the production and supply of miscanthus. It thus provides a wider audience facilitated access to LCA knowledge and promotes its use as a management and reporting tool in bio‐based industries. Abstract : Miscanthus cultivation in Europe is currently expanding. In light of GHG reduction targets, life cycle assessments become imperative. Due to the variation in biophysical conditions and management approaches, this can be time‐consuming. This study suggests a simplified model for computation of GHG emissions related to miscanthus cultivation across European condition. ​